PENGARUH FINANCIAL LITERACY DAN FINANCIAL BEHAVIOR TERHADAP PERILAKU KONSUMTIF (MAHASISWA ANGKATAN 2019 PROGRAM STUDI PENDIDIKAN EKONOMI FKIP UNDANA) - Taneo, Riky Ridkar; Data, Ari; br. Simanungkalit, Erika Feronika (Universitas Nusa Cendana, 2024)
This research aims to determine the influence of financial literacy, the influence of financial behavior and the joint influence of financial literacy and financial behavior on the consumer behavior of students class of 2019, Economic Education Study Program, Faculty of Teacher Training and Education, Nusa Cendana University. This research method is quantitative. The total population is 125 students with a sample of 95 samples calculated using the Slovin formula. In this research, the data analysis technique used is multiple linear regression analysis with the help of SPSS version 27. The research results show that there is a negative and significant partial influence on the financial literacy variable and there is a negative and significant partial influence on the financial behavior variable and there is a simultaneous simultaneous influence. positive and significant financial literacy and financial behavior variables on student consumptive behavior. Keywords: Financial Literacy, Financial Behavior, Consumptive Behavior